Feline Leishmaniosis: A Retrospective Study of Seroprevalence in Cats in the Campania Region, Southern Italy - Laura Cortese; Giulia Abate; Pasquale Santoro; Elvira Improda; Gianmarco Ferrara; Vincenzo Lucidi; Antonio Sica; Giuseppe Iovane; Serena Montagnaro (Animals, 2025)
Feline leishmaniasis (FeL), caused by Leishmania infantum, is increasingly reported in areas of endemic Mediterranean canine leishmaniasis (CanL), making it an emerging feline disease. This cross-sectional study investigated L. infantum seroprevalence and risk factors in 229 domestic cats from the Campania region of southern Italy, a CanL endemic area, between January 2023 and December 2024. Serum samples were tested for L. infantum antibodies (IFAT) and for FIV/FeLV. Seropositivity (IFAT titre ≥ 1:40) for FeL was detected in 12/229 (5.2%) of the cats tested. No statistically significant correlation was found between seropositivity for L. infantum and the variables considered. However, outdoor cats and FIV/FeLV-seropositive cats had higher prevalence rates: 10.6% and 7.4%, respectively. Of the 12 seropositive cats, 7 (58.3%) had an antibody titre of 1:40, 2 (16.6%) of 1:80 and 3 (25.0%) a titre of 1:160. Of the 12 cats positive for FeL, 2 (16.6%) were also positive for FIV. Our results confirm the exposure to L. infantum and the serological response in cats from southern Italy. The low prevalence could be due to owners using mosquito control products in the household that would also protect cats. Further investigation is essential to clarify risk factors and improve our understanding of the epidemiology of FeL in this endemic area.